Analisis Strategi Kompetitif dan Kelayakan Bisnis Adreena Shoes dalam Menghadapi Persaingan Industri Sepatu Online - Rafik Yusup; Hani Humaeriyah (INDO PUBLISHING, 2026)
This study analyzes the competitive strategy and business feasibility of Adreena Shoes amidst the fierce competition in the digital footwear market. While the industry offers massive opportunities, the low barrier to entry has created a saturated market. Using a descriptive qualitative approach, this research dissects how Adreena Shoes navigates this landscape through differentiation and multi-aspect feasibility analysis. The findings reveal that Adreena Shoes successfully occupies a strategic